2020
DOI: 10.1002/ange.201914527
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Mo−CN Bond Breakage in Octacyanomolybdate Leading to Spin Triplet Trapping

Abstract: The photoinduced properties of the octacoordinated complex K4MoIV(CN)8⋅2 H2O were studied by theoretical calculations, crystallography, and optical and magnetic measurements. The crystal structure recorded at 10 K after blue light irradiation reveals an heptacoordinated Mo(CN)7 species originating from the light‐induced cleavage of one Mo−CN bond, concomitant with the photoinduced formation of a paramagnetic signal. When this complex is heated to 70 K, it returns to its original diamagnetic ground state, demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The octacyanomolybdate(IV) anion was previously demonstrated to behave as an intrinsic photomagnetic chromophore in several bimetallic CN-bridged systems. [101][102][103] Therefore we decided to study the photomagnetic properties of 1Mn and 1Mn•8H2O at low temperatures. Both compounds strongly respond to 450 nm irradiation at 10 K with a 13-fold increase of magnetization in the case of 1Mn and a 16-fold increase for 1Mn•8H2O (Figure S26).…”
Section: Resultsmentioning
confidence: 99%
“…The octacyanomolybdate(IV) anion was previously demonstrated to behave as an intrinsic photomagnetic chromophore in several bimetallic CN-bridged systems. [101][102][103] Therefore we decided to study the photomagnetic properties of 1Mn and 1Mn•8H2O at low temperatures. Both compounds strongly respond to 450 nm irradiation at 10 K with a 13-fold increase of magnetization in the case of 1Mn and a 16-fold increase for 1Mn•8H2O (Figure S26).…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Pinkowicz and Mathonière et al found that light irradiation can induce the singlet to triplet transition in K 4 [Mo IV (CN) 8 ] accompanied by reversible dissociation/recombination of the Mo-CN bonds. 44 It is worth mentioning that the observed photoinduced triplet state was quite stable for several hours even at room temperature. Although the singlet (S = 0) to triplet (S = 1) state transition of the building block of [W IV (CN) 8 ] 4− was reported in a {Mn 2 W} 1D chain 57 and two {Mn 2 W} 3D networks, 58,59 the number of [W IV (CN) 8 ] 4− based compounds exhibiting photoinduced singlet to triplet transitions is still limited.…”
Section: Introductionmentioning
confidence: 93%
“…This is not only due to the variable dimensionalities of its architecture but also its characteristic photomagnetic behavior showing the singlet (S = 0) to triplet (S = 1) transition. [44][45][46][47][48][49][50][51][52][53][54][55][56] The photomagnetic action of octacyanotungstate(IV) is related entirely to itself in contrast to other photoinduced W-3d systems. Very recently, Pinkowicz and Mathonière et al found that light irradiation can induce the singlet to triplet transition in K 4 [Mo IV (CN) 8 ] accompanied by reversible dissociation/recombination of the Mo-CN bonds.…”
Section: Introductionmentioning
confidence: 99%
“…5) 32,35,60 or the photodissociation of the single cyanide leading to a reduction of the coordination number to 7. 34,57 Overall, both MMCT and LIESST mechanisms lead to an increase of magnetic susceptibility in the χ M T (T ) plots due to the formation of ferromagnetically coupled domains, but the similarity ends there. 27 The photomagnetic effect following the MMCT mechanism does not produce any additional spins, just relocates them (the M S after photoirradiation remains constant), and usually progresses much faster.…”
Section: Magnetic and Photomagnetic Studiesmentioning
confidence: 99%
“…Nevertheless, the latest studies confirming the unquestionable presence of the photomagnetic effect for the octacyanidomolybdate salts [56][57][58][59][60] prompt us to investigate the photomagnetic effect in Cu(II)-Mo(IV) ionic systems. In addition, they can be a platform for simultaneous theoretical and experimental studies on the photomagnetic effect, which has not been used so far due to computational limitations (too large complexity of the systems) or a lack of suitable samples.…”
Section: Introductionmentioning
confidence: 99%